Accounting for Emotional Value: A Review in Disability Organizations - Tirado-Valencia, Pilar; Ayuso, Silvia; Fernández-Rodríguez, Vicente (Frontiers in Psychology, 2021)
The aim of this paper is to examine how disability organizations account for the emotional value they create for their stakeholders. Based on a review of the literature on emotional value measurement in third sector organizations working in the disability sector, we investigate to what extent emotional value is considered in their social accounting process and what type of value variables, indicators and proxies are used. The results reveal that the analysis of some quality of life domains provides appropriate evidence to represent the emotional value generated by these organizations but that there is a great dispersion in applied instruments and methodologies. The study improves the knowledge and understanding of existing approaches to capture the emotional component of social value creation and contributes to its standardization. Our analysis has implications for the management of disability organizations that can use social accounting to evaluate their performance and improve their effectiveness and efficiency, showing a more complete picture of the social value generated. Likewise, it can be an instrument to make the contribution and social benefits of these organizations visible in all their breadth, improving transparency and legitimacy.